2012
DOI: 10.1021/np200756f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB-Dependent Cytokine and Inducible Nitric Oxide Synthesis by the Macrocyclic Ellagitannin Oenothein B in TLR-Stimulated RAW 264.7 Macrophages

Abstract: Immunomodulatory effects of oenothein B (1), a macrocyclic ellagitannin from various Onagraceae species, have been described previously. However, the mechanisms underlying the anti-inflammatory activity of 1 have not been fully clarified. The effects of 1 were investigated on inducible nitric oxide synthase, TLR-dependent and TLR-independent signal transduction cascades, and cytokine expression using murine macrophages (RAW 264.7). Compound 1 (10-60 μg/mL) reduced NO production, iNOS mRNA, and iNOS protein lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
(55 reference statements)
1
19
0
1
Order By: Relevance
“…Previous research on the biological activities of OeB has mainly been in vitro (Ducrey, Marston, Göhring, Hartmann, & Hostettmann, 1997;Schmid et al, 2012;Silva et al, 2014;Yoshimura et al, 2012). However, it has been reported that orally administered OeB can inhibit Ehrlich ascites tumors, as well as reduce neuroinflammation in the brain during systemic inflammation (Okud et al, 1986;Okuyama et al, 2013), demonstrating the potential efficacy of orally administered OeB.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the biological activities of OeB has mainly been in vitro (Ducrey, Marston, Göhring, Hartmann, & Hostettmann, 1997;Schmid et al, 2012;Silva et al, 2014;Yoshimura et al, 2012). However, it has been reported that orally administered OeB can inhibit Ehrlich ascites tumors, as well as reduce neuroinflammation in the brain during systemic inflammation (Okud et al, 1986;Okuyama et al, 2013), demonstrating the potential efficacy of orally administered OeB.…”
Section: Introductionmentioning
confidence: 99%
“…The active components responsible for the therapeutic effects of their extracts had not been well defined for a long time, but recent in vitro and in vivo studies revealed that oenothein B is one of the main biologically active components present in these extracts [58]. Detailed in vitro examination showed that oenothein B has anti-inflammatory activity against Toll-like receptor (TLR)-stimulated RAW 264.7 macrophages [9]; immunomodulatory activity toward human monocytic THP-1 Blue cells and human leukemia HL-60 cells [6]; and inhibitory activity against prostatic 5α-reductase and aromatase in prostate cancer cell lines PC-3 cells [10]. As part of studies on the activities of oenothein B, we earlier reported that it has anti-tumor activity against MM2 ascites tumors [11] and human oral squamous cell carcinoma [12,13], anti-oxidant activity [1], and an immunomodulatory effect on human dendritic cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been studied for antitumor, antiviral, antibacterial, antioxidant, pro-inflammatory, and anti-inflammatory properties [7], [26][31]. Oenothein B has been reported to inhibit inflammatory responses by phagocytes induced by TLR agonists and other stimulants [30], [31]. However, in the absence of additional stimulation, oenothein B promotes inflammatory responses by phagocytes.…”
Section: Introductionmentioning
confidence: 99%